Media Relations Dinas Komunikasi dan Informatika (Diskominfo) Kabupaten Karanganyar dalam Sosialisasi Program Pemerintah - Nur Laili Puspa Rohmana; Rhesa Zuhriya Briyan Pratiwi (Academic Journal of Da'wa and Communication, 2020)
The importance of media relations conducted by a number of PRs in Government Agencies has implications for government policies in accordance with the information needs of the community. One of them is at the Office of Communication and Information (Diskominfo) Karanganyar Regency related to the issue of government program socialization. This study aims to describe the media relations strategy used by the Karanganyar Regency Office of Communication and Information in the socialization of government programs. The type of research used is descriptive qualitative. Data collection techniques using observation, interviews, and documentation. The results of the study, Diskominfo Karanganyar Regency uses media relations strategies by managing relations, developing strategies, and developing networks with the media to optimize each role of each section in Diskominfo for the benefit of the socialization of government programs for the community.